HUBUNGAN SISA MAKANAN TERHADAP LAMA HARI RAWAT DAN BIAYA PASIEN DENGAN PENJAMIN JAMKESMAS DAN JAMPERSAL DIET MAKANAN BIASA DI RUANG RAWAT INAP KELAS III RSUD RADEN MATTAHER JAMBI - Iswanto Iswanto; Toto Sudargo; Yeni Prawiningdyah (Universitas Baiturrahim, 2016)
Background: Implementation of food is part of the activities of nutrition services in hospitals especially in the inpatient unit. Level of patient satisfaction with the quality of food will affect the food consumed. Satisfaction is low impact on the quality of food resulted in the food wasted of the food provided. Reflect food wasted nutrients intake is not adequate impact to patient malnutrition. Malnutrition can be affect the length of stay longer and higher patient costs. To identify the relationship food wasted to the length of stay in hospitalization and costs of patients with Jamkesmas and Jampersal who got regular diet in the ward class III at Raden Mattaher Jambi Hospital. Methods: This was an observational study with cross sectional design. The study subjects were patients admitted to the ward class III at Raden Mattaher Jambi Hospital in January to March 2013. Data measured by weighing the food waste using a electronic kitchen scale. Data were analyzed by univariate and bivariate. Results: Statistical analysis showed that there was no significant correlation between the rest of staple foods, vegetables and vegetable side dish with a length of stay (p> 0.05), whereas significant association between the animal side dish and fruit with a length of stay (p <0,05). There is no significant correlation between staple food, animal dishes, vegetable side dishes, vegetables and fruits with the average cost for treatment responders (p> 0,05). Result: The average food wasted varies according to the type of food. There is a significant relationship between the animal and fruit with a side dish of length of stay and there was no significant relationship between staple food scraps, animal dishes, vegetable side dishes, vegetables and fruits with the average cost of the respondent during in the treatment. Keywords: Food wasted, length of stay, patient costs, Jamkesmas and Jampersal